The evolution of jumping performance in anurans: morphological correlates and ecological implications - Gomes, F. R. [UNESP]; Rezende, E. L.; Grizante, M. B.; Navas, C. A. (Wiley-Blackwell, 2009)
We investigated the evolution of anuran locomotor performance and its morphological correlates as a function of habitat use and lifestyles. We reanalysed a subset of the data reported by Zug (Smithson. Contrib. Zool. 1978; 276: 1-31) employing phylogenetically explicit statistical methods (n = 56 species), and assembled morphological data on the ratio between hind-limb length and snout-vent length (SVL) from the literature and museum specimens for a large subgroup of the species from the original paper (n = 43 species). Analyses using independent contrasts revealed that classifying anurans into terrestrial, semi-aquatic, and arboreal categories cannot distinguish between the effects of phylogeny and ecological diversification in anuran locomotor performance. However, a more refined classification subdividing terrestrial species into 'fossorials' and 'non-fossorials', and arboreal species into 'open canopy', 'low canopy' and 'high canopy', suggests that part of the variation in locomotor performance and in hind-limb morphology can be attributed to ecological diversification. In particular, fossorial species had significantly lower jumping performances and shorter hind limbs than other species after controlling for SVL, illustrating how the trade-off between burrowing efficiency and jumping performance has resulted in morphological specialization in this group.
Keywords: anura; comparative phylogenetic method; ecological morphology; frogs; habitat; adaptation; locomotor performance